PEMBUATAN FRUIT LEATHER DARI CAMPURAN BUAH SIRSAK (Annoma muricata L.)DAN BUAH MELON (Cucumis melo L.) - Andika Pranata Risti; Netti Herawati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Theaim of this study wasto get the best treatment fruit leather from mixed soursop (Annoma muricata L.) and melon (Cucumis melo L.). The study used a Complete Randomized Design (CRD) with 6 treatments and 3 replications.The treatments were SM1 (soursop 100 : melon 0), SM2 (soursop80 : melon 20), SM3 (soursop60 : melon40), SM4 (soursop40 : melon60) SM5 (soursop20 : melon80) and SM6 (soursop 0 : melon 100).  The data were analyzed statistically using ANOVA and DNMRT at 5%.  Thestudyshowed that treatment significantly influence on water, ash content, degree of acidity (pH), crude fiber,and organoleptic test. The best treatment offruit leather from this research  wasSM2 which have water 12,16%, ash 0,75%, degree of acidity (pH) 3,98, crude fiber content 1,91%, , reddish yellow color,little fruit soursop and melonflavour, sweetness taste, the texture clay and overall assesment of fruit leather was  preferred by the panelist.Keywords: Fruit leather, soursop fruit and melon